THE EFFECT OF PRODUCT DIVERSIFICATION STRATEGY, FINANCIAL LEVERAGE, FIRM SIZE,AND CAPITAL STRUCTURE ON PROFITABILITY - Destya Aida Sofiatin; Trisandi Eka Putri; Sri Mulyati (JASS (Journal of Accounting for Sustainable Society), 2021)
This study aims to determine the effect of product diversification strategies, financial leverage, company size, and capital structure on profitability (Case Study of Consumer Goods Industry Sector Companies listed on the Indonesia Stock Exchange for the 2014-2018 period). In this study, using purposive sampling method, and samples that fit the criteria were 32 companies, so that 160 data were obtained on consumer goods industrial companies for the period 2014-2018. And the data were analyzed using Eviews 9 program. The method of analysis used in this research is descriptive statistical analysis, panel regression analysis and classical assumption test. The results showed the coefficient of determination R2 was 14% and the remaining 86% was explained by other variables. Partial results (t test), product diversification strategy variables and financial leverage have a positive and significant effect on profitability, firm size has a negative and significant effect on profitability. Meanwhile, capital structure has no significant effect on profitability. The simultaneous test results (F test) show that the product diversification strategy, financial leverage, company size and capital structure simultaneously affect profitability.